Processing of Moringa leaves as natural source of nutrients by optimization of drying and grinding mechanism - Ali, Muhammad Azhar; Yusof, Yus Aniza; Chin, Nyuk Ling; Ibrahim, Mohd Nordin (Wiley-Blackwell Publishing, 2017)
In this study, Moringa leaves were processed in two steps (1) drying and (2) grinding. In the first step, leaves were dried with different drying treatments including conventional, laboratory and advanced methods to optimize drying conditions in terms of maximum nutrients preservation and color quality. During the second step, leaves were ground with three different grinding mills including hammer, dry, and cutter mills to study the effect of grinding mechanism in combination with particles size and moisture content on the flowability of the powder. The flowability was measured using conventional and advanced methods including Carr Index and Cohesion Index. Oven drying at 50 °C was found to be the optimum conditions in terms of maximum nutrients and color preservation of Moringa leaves. The grinding mechanism having a substantial impact on the flowability of the powder produced in different types of mills. The effect of moisture content and particle size on Moringa leaves powder was also investigated and found that moisture content directly affects the flowability of Moringa leaves powder followed by particles size and shape. We have also noted powder sample prepared by the impact mechanism (hammer mill) with particle size 50 µm and moisture content 5% having appreciable flowability as compared to the samples processed by cutting (dry mill) and shattering (cutter mill) mechanisms. This study conveys an ultimate understanding regarding processing (drying and grinding) of Moringa leaves powder.